A Critical Exploration of African Spirituality and Democracy in Africa - Igboin, Benson O. (Journal of Africana religions, 2014)
This article investigates the spiritual dimension of African politics, a significant, real, and practical variable that has received little recognition in public discourse about the practice of democracy in Africa. I focus on the role of African spiritual agency and its cosmological implications in the development of African democracy. The article argues that African spirituality is pervasive but not sufficiently strong to meet the challenges of new political realities. Through the use of critical case analysis, the study concludes that African politicians exhibit a dual loyalty, affirming Western political theories in public discourse (in most cases) while adhering to African spiritual rituals and oaths in private. The consequences of this include undermining the dividends of democracy and encouraging the dereliction of the environment.